Dwindling diversity - Mortensen, Stina (2019)
Nepal’s rich agrobiodiversity is rapidly decreasing, as local varieties of crops are replaced by imported hybrid or improved varieties. At the same time, in light of the increasingly apparent effects of climate change, the need for a broad genetic base in order to maintain the ability to adapt to new conditions is evident. In this study, the attitudes towards and knowledge of different crop types, agrobiodiversity loss and conservation among different stakeholders are examined. The results show that farmers’ choices of crops are mainly motivated by yield and taste. Farmers are aware that local varieties are disappearing, but not about the possible longterm consequences of this loss. Conservation efforts need to take into account the economic reality of farmers and economic incentives to grow landraces should be strengthened. Continued support to community seed banks as a tool for conservation and awareness raising is indicated. As the role of landraces as a source of genetic diversity is not apparent to farmers in general, communication regarding conservation should focus on the perceived advantages of superior taste, increased food security, and potential economic benefits.